El Tratado de Prohibición de armas nucleares a la luz del DIH: ¿un avance en materia de desarme nuclear? - LOSADA SAN JUAN, Ignacio (Journal of the Spanish Institute for Strategic Studies, 2022)
Nuclear weapons have raised not only very important debates in the International Community since his own creation but also a big concern at that time and now. With the new TPAN as reference we can suggest a lot of cuestions as: Is the use of those weapons compatible with International Humanitarian Law? Could we think about that new international agreement as a decisive element to achieve the effective prohibition of nuclear weapons? Is it compatible with the previous regime? What problems could appear in there application? Does exist a general duty in order to bargue nuclear disarmament?